2000
DOI: 10.1161/01.hyp.35.3.787
|View full text |Cite
|
Sign up to set email alerts
|

Changes of Nocturnal Blood Pressure Dipping Status in Hypertensives by Nighttime Dosing of α-Adrenergic Blocker, Doxazosin

Abstract: Abstract-Abnormal nocturnal blood pressure (BP) dipping status may be partly determined by nocturnal sympathetic activity. We studied the effect of nighttime dosing of an ␣ 1 -adrenergic blocker, doxazosin, on the BP dipping status of 118 hypertensives, all of whom underwent 24-hour ambulatory BP monitoring before and after treatment. The mean nighttime/daytime ratio of systolic BP was increased (0.91 after therapy versus 0.89 at baseline, PϽ0.05). The patients were initially divided into 4 groups on the basis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
92
1
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 147 publications
(101 citation statements)
references
References 33 publications
5
92
1
3
Order By: Relevance
“…However, it is as yet unknown whether this narrowing of PP induced by dual blockade of the renin-angiotensin system will translate into a long-term reduction in microvascular complications. Several researchers have demonstrated that it is possible to restore the normal circadian BP pattern in 'non-dipper's with selective antihypertensive therapy directed towards an elevated night BP [37][38][39][40]. Interestingly, this approach has been reported to reduce 24 h albumin excretion rate in microalbuminuric patients with essential hypertension, thus suggesting an increased organoprotective effect of reestablishing the normal diurnal BP rhythm [39].…”
Section: Discussionmentioning
confidence: 99%
“…However, it is as yet unknown whether this narrowing of PP induced by dual blockade of the renin-angiotensin system will translate into a long-term reduction in microvascular complications. Several researchers have demonstrated that it is possible to restore the normal circadian BP pattern in 'non-dipper's with selective antihypertensive therapy directed towards an elevated night BP [37][38][39][40]. Interestingly, this approach has been reported to reduce 24 h albumin excretion rate in microalbuminuric patients with essential hypertension, thus suggesting an increased organoprotective effect of reestablishing the normal diurnal BP rhythm [39].…”
Section: Discussionmentioning
confidence: 99%
“…We previously reported that nighttime dosing with an a-blocker, doxazosin, markedly reduced nocturnal BP in nondippers and reverse dippers in uncomplicated hypertensive patients. 50 Recently, the dramatic usefulness of new strategies to manipulate autonomic function, such as baroreflex activation therapy or renal denervation in resistant hypertension, has been reported. 51,52 New frontiers in the treatment of hypertension are therefore promising in terms of their potential for improving diurnal BP variation.…”
Section: Treatment Of Nocturnal Bp Increasesmentioning
confidence: 99%
“…6,7 A possible explanation of the nocturnal decrease in BP is that it results from a reduction of sympathetic nervous activity and impaired circadian rhythm in sympatho-vagal balance during sleep. 8,9 We aimed to assess whether ANS activity indices and their changes over 2 years, as evaluated by 24-h HRV, were associated with a shift to non-dipper status among subjects identified as dippers at study entry in a general elderly population not treated for hypertension.…”
Section: Introductionmentioning
confidence: 99%